Regularization of f(T) Gravity Theories and Local Lorentz Transformation - Gamal G. L. Nashed (Advances in High Energy Physics)
We regularized the field equations of f(T) gravity theories such that the effect of local Lorentz transformation (LLT), in the case of spherical symmetry, is removed. A “general tetrad field,” with an arbitrary function of radial coordinate preserving spherical symmetry, is provided. We split that tetrad field into two matrices; the first represents a LLT, which contains an arbitrary function, and the second matrix represents a proper tetrad field which is a solution to the field equations of f(T) gravitational theory (which are not invariant under LLT). This “general tetrad field” is then applied to the regularized field equations of f(T). We show that the effect of the arbitrary function which is involved in the LLT invariably disappears.